2022
DOI: 10.1126/sciadv.add9468
|View full text |Cite
|
Sign up to set email alerts
|

TENT5 cytoplasmic noncanonical poly(A) polymerases regulate the innate immune response in animals

Abstract: Innate immunity is the first line of host defense against pathogens. Here, through global transcriptome and proteome analyses, we uncover that newly described cytoplasmic poly(A) polymerase TENT-5 (terminal nucleotidyltransferase 5) enhances the expression of secreted innate immunity effector proteins in Caenorhabditis elegans . Direct RNA sequencing revealed that multiple mRNAs with signal peptide–encoding sequences have shorter poly(A) tails in tent-5 –deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 124 publications
12
30
0
Order By: Relevance
“…Most mRNAs with poly(A) tails elongated after vaccination in WT BMDMs, but not Tent5a Flox/Flox / Tent5c -/- BMDMs, (ED Fig. 5b) encode extracellular proteins translated at the endoplasmic reticulum (ER), in line with previous findings regarding TENT5A/C substrates 26,27 . Notably, mRNA-1273 also encodes an ER-targeted protein, which, as we show, hijacks TENT5s to extend its poly(A) tail.…”
Section: Mainsupporting
confidence: 89%
See 4 more Smart Citations
“…Most mRNAs with poly(A) tails elongated after vaccination in WT BMDMs, but not Tent5a Flox/Flox / Tent5c -/- BMDMs, (ED Fig. 5b) encode extracellular proteins translated at the endoplasmic reticulum (ER), in line with previous findings regarding TENT5A/C substrates 26,27 . Notably, mRNA-1273 also encodes an ER-targeted protein, which, as we show, hijacks TENT5s to extend its poly(A) tail.…”
Section: Mainsupporting
confidence: 89%
“…They included MHC components ( H2-K1, H2-D1, H2-T23, B2m ), serum complement components ( C1qb, C1qc ), lysosomal proteins ( Lamp1, Laptm5 ), and innate immune response genes ( Ctsb, Ctsd, ApoE, Lyz2, Cst3, Ctss ). Remarkably, in our previous study on BMDMs activated with LPS 26 , a similar set of transcripts was revealed to be substrates of TENT5A/TENT5C non-canonical poly(A) polymerases. Therefore, we examined gene expression changes of all known non-canonical poly(A)/poly(U) polymerases and found that Tent5a is the only polymerase that is significantly induced at vaccine injection sites and after vaccine treatment in BMDMs ( Fig.…”
Section: Mainmentioning
confidence: 59%
See 3 more Smart Citations